2012
DOI: 10.1177/0886260512468239
|View full text |Cite
|
Sign up to set email alerts
|

How Much Does “How Much” Matter? Assessing the Relationship Between Children’s Lifetime Exposure to Violence and Trauma Symptoms, Behavior Problems, and Parenting Stress

Abstract: The study explores whether and how lifetime violence exposure is related to a set of negative symptoms: child internalizing and externalizing behavior problems, child trauma symptoms, and parenting stress. Using a large sample of violence-exposed children recruited to participate in intervention research, the study employs different methods of measuring that exposure. These include total frequency of all lifetime exposure, total frequency of lifetime exposure by broad category (i.e., assault, maltreatment, sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 41 publications
2
43
1
1
Order By: Relevance
“…Hickman and colleagues suggest that it may be the mix of the type of exposure experiences that has the greatest negative effect on children. 61 Although we did not have longitudinal data, our results suggest there may be a strong impact of cumulative indirect violence exposure on externalizing behavior in children, as well as a significant effect of direct violence exposure (e.g., physical aggression). Findings are consistent with past research indicating that multiple types of violence exposure, experienced both within the family and in the neighborhood 80, 81 both co-occur and multiplicatively contribute to behavior.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Hickman and colleagues suggest that it may be the mix of the type of exposure experiences that has the greatest negative effect on children. 61 Although we did not have longitudinal data, our results suggest there may be a strong impact of cumulative indirect violence exposure on externalizing behavior in children, as well as a significant effect of direct violence exposure (e.g., physical aggression). Findings are consistent with past research indicating that multiple types of violence exposure, experienced both within the family and in the neighborhood 80, 81 both co-occur and multiplicatively contribute to behavior.…”
Section: Discussionmentioning
confidence: 67%
“…As few studies have addressed the risk for externalizing behaviors due to cumulative violence exposure, it is an important next research step to expand our understanding of the reciprocal relation between cumulative violence exposure and externalizing behaviors. 59,61 Further, an individual's temperament or personality traits, as well as social support and a variety of other factors including age and gender, are also likely moderators of the relationship between both acute and chronic stressors, such as exposure to violence and externalizing behaviors, and should be examined. Finally, there should be an emphasis on identification of potential sources of buffering for the effects of exposure to violence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Children exposed to domestic violence (DV) have increased risk for externalizing behavior problems, internalizing behavior problems, and trauma symptoms (Evans, Davies, and DiLillo, 2008), while childhood exposure to community violence has been shown to be strongly related to both externalizing behavior problems and posttraumatic stress disorder (PTSD) (Fowler et al, 2009). In our own work examining violence exposure among a sample of families engaged with community-based service organizations, we found that exposure to multiple forms of violence strongly predicted child internalizing and externalizing behavior problems and trauma symptoms among the subsample of children with any victimization history (Hickman et al, 2013).…”
Section: Acknowledgmentsmentioning
confidence: 99%